Development Of Class X Ecosystem E-Catalog at SMA Negeri 12 Semarang - Tri Astuti, Diyah Ayu; Rudyatmi, Ely (Universitas Negeri Semarang, 2024)
Digital technology has not yet been integrated to create an innovative learning media ecosystem. Utilization of local potential as a medium for ecosystem learning is still rarely done. Student learning outcomes in ecosystem Materi are still less than optimal. This can be seen from the scores of many students who are still incomplete. So it is necessary to develop an E-Catalog for class X ecosystems at SMA Negeri 12 Semarang. The aim of this research is to analyze the validity, practicality and effectiveness of the E-Catalog. This type of research is research and development with an ADDIE design (Analyze, Design, Development, Implementation, Evaluate). Media validity is measured using a validity assessment questionnaire by Materi and media experts. The practicality of the media is measured by teacher and student response questionnaires. The effectiveness of the Ecosystem E-Catalog is measured by learning outcome tests. Data were analyzed using descriptive percentage techniques. The results of the validator assessment stated that the Ecosystem E-Catalog media was very valid. In the small scale trial, 50% of students thought the Ecosystem E-Catalog was very practical and 50% of students thought it was practical. In a large-scale test, teachers and 69% of students thought the Ecosystem E-Catalog was very practical. All students have completed learning about Ecosystem materi . The Ecosystem E-Catalog is very valid, very practical and effectively used for teaching and learning activities at SMA Negeri 12 Semarang.